Slit and Receptor Tyrosine Phosphatase 69D Confer Spatial Specificity to Axon Branching via Dscam1 - Dascenco, Dan (Cell, 2015)
Axonal branching contributes substantially to neuronal circuit complexity. Studies in Drosophila have shown that loss of Dscam1 receptor diversity can fully block axon branching in mechanosensory neurons. Here we report that cell-autonomous loss of the Receptor-Tyrosine-Phosphatase 69D (RPTP69D) and loss of midline-localized Slit inhibit formation of specific axon collaterals through modulation of Dscam1 activity. Genetic and biochemical data support a model in which direct binding of Slit to Dscam1 enhances the interaction of Dscam1 with RPTP69D, stimulating Dscam1 dephosphorylation. Single growth cone imaging reveals that Slit/RPTP69D are not required for general branch initiation, but instead promote the extension of specific axon collaterals. Hence, while regulation of intrinsic Dscam1-Dscam1 isoform interactions is essential for formation of all mechanosensory-axon branches, the local ligand-induced alterations of Dscam1 phosphorylation in distinct growth cone compartments enable the spatial specificity of axon collateral formation.